PENGAMBILAN KEPUTUSAN PETANI DALAM BERUSAHATANI LABU SIAM (Sechium edule) (Studi Kasus di Kecamatan Pasirjambu, Kabupaten Bandung) - Muhamad Rizky Wibowo; Hepi Hapsari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Since 2016 there has been a significant shift in farming to chayote commodities in Pasirjambu District, Bandung Regency. Gapoktan Regge Regeneration is a pioneer of chayote farming. The purpose of this study was to determine the factors most considered by farmers in choosing chayote farming and the feasibility of chayote farming. The research method used is qualitative with a case study involving 15 informants selected by the snowball sampling technique. Data were analyzed using AHP (Analytical Hierarchy Process). The results showed that the most considered factors were economic factors (0,623), followed by social factors and then technical factors in third place. At the criteria level, the profit criteria (0,320) are the criteria that are most considered by farmers to cultivate chayote and after that are the criteria for market availability, farming experience, age, availability of capital, cultivation ability, tools, education level, and availability of seeds at the lowest level.